NLRP6‐caspase 4 inflammasome activation in response to cariogenic bacterial lipoteichoic acid in human dental pulp inflammation. (20th January 2021) - Tian, X. X.; Li, R.; Liu, C.; Liu, F.; Yang, L. J.; Wang, S. P.; Wang, C. L.
Abstract: Aim: To explore the presence and function of NLRP6‐caspase 4 inflammasome in human pulp tissue and human dental pulp cells (HDPCs). Methodology: Pulp tissue was collected from freshly extracted human caries‐free third molars and third molars with irreversible pulpitis. Quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blot were performed to assess the expression of NLRP6‐caspase 4 inflammasome. HDPCs were prepared from normal human pulp tissues and challenged with Porphyromonas gingivalis LPS. Enzyme‐linked immunosorbent assay (ELISA) and qRT‐PCR were performed to assess if LPS can upregulate NLRP6 and caspase‐4. HDPCs were further challenged with LPS followed with cytosolic Streptococcus mutans lipoteichoic acid (LTA). SiRNA targeting NLRP6 and Casp4 and pharmacology inhibitor Ac‐FLTD‐CMK and MCC950 were used to assess if Streptococcus mutans LTA can activate the NLRP6 but not the NLRP3 inflammasome. Western blot and ELISA were performed to evaluate inflammasome activation. The Student's t ‐test and one‐way anova were used for statistical analysis. Results: NLRP6‐caspase 4 inflammasome was upregulated and activated in inflamed human dental pulp tissue. In HDPCs, Porphyromonas gingivalis LPS upregulated the expression of NLRP6, CASP1 and CASP4 in a type I interferon dependent manner. After LPS priming, cytosolic Streptococcus mutans LTA triggered NLRP6‐caspase 4 inflammasome activation. Knockdown of NLRP6 or CASP4 using siRNA or using pharmacology inhibitor Ac‐FLTD‐CMK but not MCC950 efficiently suppressed inflammasome activation by cytosolic LTA. Conclusions: NLRP6‐caspase 4 inflammasome may play an important role in pulp inflammation and immune defence. Inflammatory caspases represent a pharmacological target to restrain pulpal inflammation.